Behavior of fascicle and tendinous tissue of medial gastrocnemius muscle during rebound exercise of ankle joint - Sugisaki, N.; Kanehisa, H.; Kawakami, Y.; Fukunaga, T. (International Journal of Sport & Health Science, 2005)
This study aimed to investigate the mechanisms of mechanical work and power enhancement of muscle-tendon complex (MTC) in rebound exercise by quantifying in vivo behavior of fascicle and tendinous tissue of human medial gastrocnemius muscle (MG). Subjects jumped on a sledge apparatus using only ankle joint with the following two conditions: plantar flexion without counter movement (PFJ) and rebound jumping from a height of 26 cm (RJ). The behavior of fascicle and tendinous tissue of MG in vivo was determined using ultrasonography. The relative contribution of tendinous tissue to the mechanical work of MTC during plantar flexion phase (PF phase) was 85% in RJ. The maximal mechanical power of tendinous tissue during the PF phase in RJ was about three times greater compared to that in PFJ. There was no significant difference in the mechanical power of fascicle during PF phase between the two conditions, while the mechanical work of fascicle in PFJ was less than that in the PF phase of RJ. In RJ, fascicle was stretched during the dorsiflexion phase. These findings indicated that, in rebound exercise using ankle joint, (1) the enhancement of mechanical work and power of MTC was due to the reuse of elastic energy stored in tendinous tissue during dorsiflexion phase, and (2) fascicles were stretched during dorsiflexion phase.